The search for blue transitions in aquaculture-dominant countries - Richard S. Cottrell; Danielle M. Ferraro; Gordon D. Blasco; Benjamin S. Halpern; Halley E. Froehlich (John Wiley & Sons Ltd., 2025)
The capacity for aquaculture to provide an alternative source of fish and seafood to capture fisheries was once promoted as a tool to reduce demand for wild fish and thus tackle overfishing. To date, there is little evidence to suggest that aquaculture growth has successfully reduced fishing effort on wild populations. Recent theory on “blue transitions” suggests that displacement may only occur as aquaculture production surpasses that of capture operations. Yet, there has been no systematic attempt to understand whether aquaculture-driven fisheries displacement has occurred in countries where aquaculture is now the dominant production form. We investigate the role of aquaculture on fisheries landings in these “aquaculture-dominant” countries using national-level production, trade, consumption and socioeconomic data from 1980 to 2017. Importantly, we find that aquaculture growth is associated with fisheries decline in aquaculture-dominant countries, but the marginal effects of aquaculture have a far weaker influence on wild-caught landings than other promoting factors, such as fish consumption and trade. Further, our qualitative analysis of the state of wild fisheries in aquaculture-dominant nations suggests that overexploitation continues to be pervasive and that any minimal displacement effects from aquaculture are unlikely to have offset the environmental impacts imposed by the growing sector. The rise of aquaculture as an alternative production form can provide valuable insights for growing industries developing sustainable new foods. Unless coupled with effective food consumption policy, such products may simply add to rather than displace the environmental impacts of human food production.